Aspek-Aspek Prioritas Manajemen Wakaf di Indonesia - Ali, Khalifah Muhamad; Yuliani, Meida; Mulatsih, Sri; Abdullah, Zaki (AL-FALAH : Journal of Islamic Economics, 2018)
One of the most potential Islamic economic instruments in Indonesia to improve the quality of people's welfare is waqf. This is supported by the demographic condition of Indonesia which majority is Muslim with big potential of waqf. Practically, the optimization of the potential is not yet in maximum condition and productive. The priority analysis of problems, solutions and strategies in waqf management in Indonesia is done in this research in order to maximize priority to made waqf management is more productive. This study uses primary and secondary data using Analytical Network Process (ANP) method. The result of the analysis shows that the lack of competence and lack of nazhir professionalism become the priority of the internal waqf management problem. While the priority of external problems is the lack of society understanding about waqf and also regulations that are less supportive. Improving the competence, guidance and mentoring of nazhir becomes the priority of internal solutions, while the priority of external solution is the optimization of the role of Badan Wakaf Indonesia (BWI) by improve the regulation by looking at the reality. Short term priority strategy that can be done is to socialize and educate about waqf to all elements.